1994
DOI: 10.1083/jcb.125.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor antibody BR96 blocks cell migration and binds to a lysosomal membrane glycoprotein on cell surface microspikes and ruffled membranes.

Abstract: Abstract. BR 96 is an internalizing antibody that binds to Lewis Y (LeY), a carbohydrate determinant expressed at high levels on many human carcinomas (Hellstr6m, I., H. J. Garrigues, U. Garfigues, and K. E. Hellstr6m. 1990. Cancer Res. 50:2183-2190. Breast carcinoma cell lines grown to confluence bind less BR96 than subconfluent cultures (Garrigues, J., U. Garrigues, I. Hellstr6m, and K. E. Hellstr6m. 1993. Am. J. Path. 142:607-622). However, when the confluent cells are induced to migrate by scratch woundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Antibodies BR55-2 and BR15-6A directed to LeY significantly decreased the adhesion in a dose-dependent fashion, implicating the involvement of LeY in adhesion of these breast carcinoma cells. These data indicate that different human adenocarcinoma cells interact with EC via E-selectin-mediated and E-selectin-independent pathways in agreement with previously published reports that some invasive breast carcinoma cells do not interact with TNF-c(x-stimulated EC under dynamic conditions, but adhere to resting and stimulated EC via an E-selectin independent mode following static incubation (12,13).…”
Section: Performing Organization Name(s) and Address(es)supporting
confidence: 81%
“…Antibodies BR55-2 and BR15-6A directed to LeY significantly decreased the adhesion in a dose-dependent fashion, implicating the involvement of LeY in adhesion of these breast carcinoma cells. These data indicate that different human adenocarcinoma cells interact with EC via E-selectin-mediated and E-selectin-independent pathways in agreement with previously published reports that some invasive breast carcinoma cells do not interact with TNF-c(x-stimulated EC under dynamic conditions, but adhere to resting and stimulated EC via an E-selectin independent mode following static incubation (12,13).…”
Section: Performing Organization Name(s) and Address(es)supporting
confidence: 81%
“…However, the biologic function of LAMP3 in migration and metastasis in tumor cells is not understood. LAMP1 was shown to be required for proper formation of membrane ruffles and filopodia in migrating tumor cells (45) and it is possible that LAMP3 exerts a similar function in response to hypoxia. A role for LAMP3 in cell-cell adhesion has also been proposed as it is a highly glycosylated protein that is often localized to the cell surface of tumor cells (42,46), and other LAMP family members have already been implicated in cell adhesion (47).…”
Section: Discussionmentioning
confidence: 99%
“…As Garrigues et al (1994) had demonstrated that the lysosomal glycoprotein LAMP-1 was the major Ley-bearing component in 3396 breast cancer cells, we examined the expression of LAMP-1 in ovarian cancer cell lines and its possible relationship to the faster-migrating Ley-reactive species. By radioimmunoprecipitation analysis, OVCAR-3 cells were found to be LAMP-1 negative (Fig.…”
Section: Biochemical Ident$cation Of Ley-bearing Antigens In Ovunan Cmentioning
confidence: 99%